Penerapan Model GI-GDL untuk Meningkatkan Ketuntasan Belajar Fisika dalam Proyek Penguatan Profil Pelajar Pancasila - Hartini Dewi (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Abstract: Abstract: In order for students to be able to investigate a topic systematically and analytically, students' understanding of a concept in learning can last longer because they understand the concept independently, through their activeness in digging for information. This is what makes it possible for teachers to apply the investigative group learning model along with the discovery learning guide model which was further merged into the name of the GI-GDL model in an effort to complete physics learning and create a profile of Pancasila students in P5. The purpose of this study is first to determine the percentage of completeness of learning physics and P5 in the independent learning curriculum using the GI-GDL model. Second, to find out the percentage of implementation of the investigation group learning model accompanied by the guide discovery learning method in the completion of learning physics in the application of the independent learning curriculum. Third, describe the achievement of the project to strengthen the profile of Pancasila students in an independent curriculum using the GI-GDL model. The research method used is R&D level two, with a qualitative descriptive type of research. Metode pengambilan data menggunakan tes dan nontes. Tehnik analisa data berupa deskriptif kualitatif dan kuantitatif. The results of the study obtained that the percentage of completeness of learning physics and P5 is 100%. The percentage of implementation of the application of the investigative group learning model accompanied by the guide discovery learning method in the completeness of learning physics and P5 in the application of the independent learning curriculum was 95.67%. The description of the achievement of P5 in an independent curriculum using the GI-GDL model is the achievement of meaningful learning in independence. Keywords: investigative group model, discovery learning guide